2018
DOI: 10.1101/309070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common genetic variants contribute to risk of rare severe neurodevelopmental disorders

Abstract: There are thousands of rare human disorders caused by a single deleterious, protein-coding genetic variant 1. However, patients with the same genetic defect can have different clinical presentation 2–4, and some individuals carrying known disease-causing variants can appear unaffected 5. What explains these differences? Here, we show in a cohort of 6,987 children with heterogeneous severe neurodevelopmental disorders expected to be almost entirely monogenic that 7.7% of variance in risk is attributable to inhe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 42 publications
6
71
0
Order By: Relevance
“…To date, many researchers have worked to reveal interactions between genetic variants and disease phenotypes. Recently, COMMUNICATIONS BIOLOGY | https://doi.org/10.1038/s42003-020-0755-1 ARTICLE COMMUNICATIONS BIOLOGY | (2020) 3:33 | https://doi.org/10.1038/s42003-020-0755-1 | www.nature.com/commsbio genome-wide quantification analyses have shown that rare mutations are found in normal tissue, whereas risk variants from neurodevelopmental disorder patients are common genetic variants, implying that non-rare genetic variants may cause genetic disease in some patients [50][51][52][53][54][55] . In this study, we showed that correction of the ATP7A M1311V mutation can rescue the function of MNs derived from cells of one ALS patient of Ashkenazi Jewish descent.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many researchers have worked to reveal interactions between genetic variants and disease phenotypes. Recently, COMMUNICATIONS BIOLOGY | https://doi.org/10.1038/s42003-020-0755-1 ARTICLE COMMUNICATIONS BIOLOGY | (2020) 3:33 | https://doi.org/10.1038/s42003-020-0755-1 | www.nature.com/commsbio genome-wide quantification analyses have shown that rare mutations are found in normal tissue, whereas risk variants from neurodevelopmental disorder patients are common genetic variants, implying that non-rare genetic variants may cause genetic disease in some patients [50][51][52][53][54][55] . In this study, we showed that correction of the ATP7A M1311V mutation can rescue the function of MNs derived from cells of one ALS patient of Ashkenazi Jewish descent.…”
Section: Discussionmentioning
confidence: 99%
“…Current research suggests that genetic effects can overlap between syndromes that have traditionally been considered as clinically distinct. Similarly, genetic overlaps are reported between Mendelian forms of disease and more complex forms of disorder [23][24][25] . These changes in the field led us to apply an alternative approach to the investigation of molecular mechanisms underlying hearing and language within the current study.…”
mentioning
confidence: 92%
“…Factors that can disrupt neurodevelopment are not fully delineated, but a significant proportion of neurodevelopmental risk is attributed to copy number variants (CNVs) 5,6 . CNVs are structural mutations that occur when genomic regions are duplicated or deleted compared to the reference genome 7 . Several large, rare CNVs have been robustly associated with increased risk for neurodevelopmental disorders (NDDs) including intellectual disability (ID), developmental delay (DD), autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and multiple congenital anomalies 8,9 .…”
Section: Introductionmentioning
confidence: 99%